2023
DOI: 10.1038/s41467-023-39321-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolvability-enhancing mutations in the fitness landscapes of an RNA and a protein

Abstract: Can evolvability—the ability to produce adaptive heritable variation—itself evolve through adaptive Darwinian evolution? If so, then Darwinian evolution may help create the conditions that enable Darwinian evolution. Here I propose a framework that is suitable to address this question with available experimental data on adaptive landscapes. I introduce the notion of an evolvability-enhancing mutation, which increases the likelihood that subsequent mutations in an evolving organism, protein, or RNA molecule are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…using barcoded lineage tracking (8,(50)(51)(52) or mutation trap experiments (53). However, we have also shown that the important changes in this distribution will often occur in its high-fitness tail, and are poorly captured by existing heuristics like the mean mutational effect (42,54). They can also depend on external factors like the population size and the overall mutation rate.…”
Section: Discussionmentioning
confidence: 99%
“…using barcoded lineage tracking (8,(50)(51)(52) or mutation trap experiments (53). However, we have also shown that the important changes in this distribution will often occur in its high-fitness tail, and are poorly captured by existing heuristics like the mean mutational effect (42,54). They can also depend on external factors like the population size and the overall mutation rate.…”
Section: Discussionmentioning
confidence: 99%
“…These arguments are consistent with the decisive role of the stable epistatic hotspots Y501 and R498 in ACE2 binding and the presence of epistatic drift in other RBD sites that mediate immune evasion properties and may determine future "pockets" of evolutionary changes. Most recent studies have identified "evolvability-enhancing" mutations that could create a genetic background where subsequent mutations are more likely to be beneficial relative to mutations acquired on an ancestral background [131,132]. The relationships between epistatic interactions and evolution are complex and while the effects of some mutations follow predictable fitness-correlated patterns, these patterns depend on the biological system and on the physical underpinnings of particular phenotypes, such as protein binding.…”
Section: Discussionmentioning
confidence: 99%
“…In a new study published in Nature Communications , Andreas Wagner utilizes large data sets and computational tools to offer provocative ideas about the frequency, phenotypic effects, and evolutionary consequences of mutations that facilitate access to beneficial mutations and more efficient searches for fitness peaks 6 . Specifically, Wagner identifies “evolvability-enhancing” mutations that create a genetic background where subsequent mutations are more likely to be beneficial relative to mutations acquired on an ancestral background by virtue of their average mutational neighbor being of higher fitness (Fig.…”
Section: Evolvability and Its Modern Controversiesmentioning
confidence: 99%